Circular Economy can Provide a Sustainable Global Society - Mohajan, Haradhan Kumar (Journal of Economic Development, Environment and People, 2020)
Since start of the Industrial Revolution about 260 years ago, the negative effects from the traditional linear economy (LE) become threat to the stability of the economies and natural ecosystems. Strength of climate change, reduction of environment pollution and integrity of ecosystems are essential issues for survival of the global humanity. According to LE resources for production are easily available and unlimited, and after use wastes are disposable. The circular economy (CE) is an alternative to the LE where the resources may be used for as long as possible. It tries to capture the value of existing products and materials, and decreases the use of primary materials in industries. The CE is a part of environmental economics and beneficial to the society. It keeps products, components, and materials at their highest utility and maximum value at all times. At present CE is one of the most focused terms among environmental economic scientists. The aim of this study is the implementation of the sustainable development strategies and the transition from LE towards CE.